Gender differences in earnings and labor supply in early career: Evidence from Kosovo's school-to-work transition survey - Francesco Pastore; Sarosh Sattar; Erwin R. Tiongson (IZA Journal of Labor & Development, 2013)
Very little is known about gender wage disparities in Kosovo and, to date, nothing is known about how such wage disparities evolve over time, particularly during the first few years spent by young workers in the labor market. More generally, not much is known about gender wage gaps in early career worldwide, a period which is perceived to be an important determinant of the overall gender wage disparity. This paper analyzes data from the School-to-Work Transition (SWT) survey, an unusual survey conducted by the ILO between 2004 and 2006 in eight countries, including Kosovo, that documents the labor market experiences of the youngest age segment in the labor force (age 15-25 years). The results of the analysis suggest that, on average, women have lower education attainment than men but this educational disparity is masked among the sample of employed men and women who tend to be well-educated. The consequences of this dramatic segmentation of labor market participation are striking. On average, there is little or no gender wage gap. The results of the Juhn et al. (J Polit Econ 101:410-442, 1993) decomposition analysis reveals that gender wage differences are almost entirely driven by differences in characteristics (rather than either the returns to those characteristics or the residual). The greater average educational attainment of employed women, among other characteristics, tends to fully offset the gender wage gap. Not surprisingly, the returns to women's education among employed women are low because there is little variation in educational attainment among the sample of well-educated employed women. When the analysis controls for sample selection bias and heterogeneity, the returns to women's education rise, confirming the lower productivity-related characteristics of non-employed women compared to employed women. The relatively small sample constrains a fuller analysis of the emergence of the gender wage gap, which, according to a small but growing international literature, typically materializes during childbearing years.
Keywords: I21; J13; J15; J16; J24; J31; J7; P30; 330; gender wage gap and dynamics; early labor market outcomes; school-to-work transitions; earnings equations; decomposition analysis; Balkans area; Kosovo; China; Arbeitsmarktintegration; Lohnstruktur; Geschlecht; Dekompositionsverfahren; Kosovo; Südosteuropa; China